The secret servant - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2007)
Gabriel Allon, the master art restorer and sometime officer of Israeli intelligence, is summoned to undertake what appears to be a routine assignment: travel to Amsterdam to purge the archives of a murdered Dutch terrorism analyst who also happened to be an asset of Israeli intelligence. But once in Amsterdam, Gabriel soon discovers a conspiracy of terror festering in the city's Islamic underground, a plot that is about to explode on the other side of the English Channel, in the middle of London.